Overexpression of X chromosome-linked inhibitor of apoptosis by inhibiting microRNA-24 protects periodontal ligament cells against hydrogen peroxide-induced cell apoptosis - Liu, C; Chen, Z; Wang, J; Hu, H (Cellular and Molecular Biology, 2016)
Hydrogen peroxide (H2O2), a common oral clinical drug for the tooth bleaching, induces severe cell apoptosis of periodontal ligament cells (PDLCs). The excessive cell apoptosis of PDLCs impairs periodontal tissue damage and repair. However, the underlying mechanism is incompletely understood. Here, we showed that microRNA-24 (miR-24) played an important role in regulating H2O2-induced cell apoptosis of PDLCs. We found that miR-24 expression was increased in PDLCs in response to H2O2 treatment. Down-regulation of miR-24 obviously rescued H2O2-induced cell apoptosis in PDLCs. By bioinformatic analysis, X chromosome-linked inhibitor of apoptosis (XIAP) was identified as a candidate target gene of miR-24, which was further verified by the dual-luciferase reporter assay. Furthermore, the protein expression level of phosphatase and tensin homolog deleted on chromosome ten was significantly decreased by miR-24 silencing, whereas the phosphorylation of Akt was remarkably increased by miR-24 silencing. In addition, the gene silencing of XIAP significantly reduced Akt activity and blocked the protective effect of the miR-24 inhibitor against H2O2-induced cell apoptosis. Overall, our findings suggest that miR-24 plays an important role in regulating the cell survival of PDLCs through targeting XIAP.